Characteristics of Bullying Behavior and the Urgency of Islamic Education in Students' Moral Development: A Study at SMAN 28 Tangerang Regency - Abbas, Ika (TA`DIBUNA, 2026)
Bullying behavior in secondary schools is a serious issue that negatively affects students’ psychological, social, and moral development. This phenomenon not only harms the victims but also impacts the perpetrators, bystanders, and the overall school climate. Islamic education plays a strategic role in the moral development of students as part of both preventive and solution-based efforts to address deviant behaviors such as bullying. This study aims to analyze the characteristics of bullying behavior and to describe the urgency of Islamic education in shaping students' character at SMAN 28 Tangerang Regency. This research employs a mixed-methods approach with a sequential explanatory design, beginning with the collection of quantitative data through surveys and analysis using Confirmatory Factor Analysis (CFA), followed by qualitative data collection through in-depth interviews, participatory observation, and document analysis. The qualitative data were analyzed using grounded theory through open coding, axial coding, and selective coding. The findings indicate that the characteristics of bullying behavior are influenced by gender and social constructs. Male students are more likely to be involved in physical and verbal bullying, while female students are more vulnerable to relational and psychological bullying. Bystanders tend to remain passive due to social pressure, although they have the potential to become agents of change if provided with training and support. The study concludes that it is necessary to develop a model of moral development based on Islamic education that is responsive to the contextual characteristics of bullying in order to foster a safe, just, and dignified school culture.